Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(-\left(x^2-2x+1\right)=-\left(x-1\right)^2\)
\(8x^3+y^6=\left(2x+y^2\right)\left(4x^2-2xy^2+y^4\right)\)
\(x^2-16+4xy+4y^2=\left(x+2y\right)^2-16\)
\(=\left(x+2y-4\right)\left(x+2y+4\right)\)
\(\left(8x+3\right)^2-25x^2=\left(8x+3\right)^2-\left(5x\right)^2=\left(8x+3+5x\right)\left(8x+3-5x\right)=\left(13x+3\right)\left(3x+3\right)\)
=(x+2)(x+5)(x+3)(x+4)-24
=(x2+2x+5x+10)(x2+3x+4x+12)-24
=((x2+7x+11)-1)((x2+7x+11)+1)-24
=(x2+7x+11)2-12-24
=(x2+7x+11)2-25
=(x2+7x+11)2-52
=(x2+7x+11-5)(x2+7x+11+5)
=(x2+7x+6)(x2+7x+16)
=(x2+x+6+6x)(x2+7x+16)
=(x(x+1)+6(x+1))(x2+7x+16)
=(x+6)(x+1)(x2+7x+16)
Tick cho mình nhé
a)x2-2xy+y2-2x+2y
=(x2-2xy+y2-2x+2y+1)-1
=(x-y-1)2-1
=(x-y-2)(x-y)
b)x3-49x
=x(x2-72)
=x(x+7)(x-7)
c)x2-y2+6x+9
=(x2+6x+9)-y2
=(x+3)2-y2
=(x-y+3)(x+y+3)
d)x2-6x+5
=x2-5x-x+5
=x(x-5)-(x-5)
=(x-1)(x-5)
\(6x^4-11x^2+3=6x^4-9x^2-2x^2+3\)
\(=3x^2\left(2x^2-3\right)-\left(2x^2-3\right)=\left(2x^2-3\right)\left(3x^2-1\right)\)
x\(^2\)-(a+b)x+ab
= x\(^2\)-ax-bx+ab
= x(x-a) - b(x-a)
= ( x-a).( x-b)
ax-2x-a\(^2\)+2a
= x(a-2) - a(a-2)
= (a-2).( x-a)
x^2+8x+16-21
(x+4)^2-21
(x+4-căn 21)(x+4+căn 21)